Сестра снежного человека: повесть / Е. В. Артамонова - Артамонова Елена Вадимовна (Детский детектив, 2011)
Экземпляры: ОРФ (2012) / Инвентарный номер: 47964 / Цена: / Авт.знак: А 86 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6